Interpersonal Communication between Teachers and Students in Building Self-Confidence at the Izzatul Islam Bogor Foundation - Alpi Amalia; Kholil Nawawi; Fahmi Irfani (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
Students still lack confidence in communicating and demonstrating their abilities. This can occur because communication between teachers and students is not yet optimal. Therefore, interpersonal communication is crucial for building student self-confidence.This study aims to analyze interpersonal communication between teachers and students in increasing self-confidence at the Izzatul Islam Foundation. The background of this study arose because there was a problem of students having difficulty building self-confidence when adapting to a new place, so that it requires the role of teachers in building it. This study used a qualitative phenomenological method through observation, interviews and documentation. The results of this study showed that interpersonal communication carried out by teachers was interactive and supportive. Through a personal approach with attention and motivation given by teachers so that students are more comfortable, open and confident. Students also showed openness that became more confident in adapting to their environment. This study contributes to the development of interpersonal communication in Islamic education, especially in increasing students' self-confidence through effective, open, and supportive communication relationships, and serves as a reference for further research related to interpersonal communication and students' self-confidence.